(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Yakymenko S. І. Integration processes in modern primary education. In this article the author considers questions of integration processes in the modern primary school : problems and prospects. The author analyzes the main aspects , reasons and tendencies of development of integration processes that relate directly to the contents of primary education.